Den store bedstefader CHRISTIAN V OG CHRISTIAN IV-MYTEN - Hein, Jørgen (Historisk Tidsskrift, 1993)
The present study examines artifacts, orders and medals commissioned by King Christian V which "borrowed" motifs from his grandfather, Christian IV. Significant examples of this were: 1) An idea in 1671 about restoring the 1616 order of the "Armed Arm" as an alternative to the Order of the Dannebrog. 2) The image of Christian V embellished with a pigtail like his grandfather's on tokens of favour, medals, coins and reliefs, especially during the Scania War and the attempts to annex Schleswig. 3) The statues of Christian IV and Frederik 111 on horseback, which were spuriously claimed to support Danish suzerainty over Hamburg by the custodians of the Cabinet of Curiosities, one of Copenhagen's most illustrious attractions. The author argues that Christian V's revival of his grandfather's person and objectives led to the formation of the Christian IV myth of the eighteenth century.